2013
DOI: 10.1371/journal.pone.0053955
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Metabolism of Human Osteoarthritic Articular Cartilage as Modulated by Bovine Collagen Hydrolysates

Abstract: Destruction of articular cartilage is a characteristic feature of osteoarthritis (OA). Collagen hydrolysates are mixtures of collagen peptides and have gained huge public attention as nutriceuticals used for prophylaxis of OA. Here, we evaluated for the first time whether different bovine collagen hydrolysate preparations indeed modulate the metabolism of collagen and proteoglycans from human OA cartilage explants and determined the chemical composition of oligopeptides representing collagen fragments. Using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 42 publications
6
72
0
1
Order By: Relevance
“…The specific effects seems to be dependent on the collagen hydrolysate concentration, the experimental conditions (Ng et al 2007), and specific the characteristic of the tested collagen hydrolysates (Schadow et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The specific effects seems to be dependent on the collagen hydrolysate concentration, the experimental conditions (Ng et al 2007), and specific the characteristic of the tested collagen hydrolysates (Schadow et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Other in vitro experiments showed an increase of protease activity after collagen fragments supplementation (Fichter et al 2006;Jennings et al 2001). There is evidence that the effects of collagen hydrolysate depend on the concentration, the experimental conditions, (Ng et al 2007), and the characteristic of the tested collagen hydrolysates (Schadow et al 2013). However, the clinical relevance of the observed effects needs to be clarified.…”
Section: Introductionmentioning
confidence: 93%
“…In den vergangenen Jahren hat das Kollagen-Hydrolysat Eingang in die nutritive Therapie gefunden, nachdem in Tierstudien mit radioaktiv markiertem KollagenHydrolysat gezeigt werden konnte, dass eine Aufnahme sowohl der Peptide als auch des Makromoleküls in den Gelenkknorpel belegbar ist [33]. In-vitro-Studien belegen darüber hinaus eine erhöhte Kollagensyntheserate in OA-Gelenkexplants durch die Zugabe von KollagenHydrolysat in das Kulturmedium [40]. Eine geringe Zahl klinischer Studien mit eingeschränkter Evidenz konnten bisher nur uneinheitlich positive Effekte bei der Schmerzreduktion und bei der Funktionsverbesserung der OA-Gelenke nachweisen [39].…”
Section: Kollagen-hydrolysatunclassified
“…Despite the great expectations for the positive results of studies such as Bello & Oesser, 36 Schadow et al, 41 concluded in their clinical trials with radioactive proline in vitro models that even at high doses (10mg/ml), collagen does not exert a stimulatory effect on collagen biosynthesis by human cartilage, regardless of the degree of change in OA. Different results can occur between studies because of differences in applied analytical methods, species, and the age and health of the joints.…”
mentioning
confidence: 99%
“…Furthermore, the determination of the radioactive proline incorporation rate without specific separation of total proteins does not reflect the true collagen synthesis rate, since the proline enrichment in the collagen compared to other proteins is not described. However Schadow et al 41 stated that collagen hydrolysate preparations could contain therapeutically active peptides, but extensive studies are needed, as well as clinical trials, before these are applied as nutraceuticals.…”
mentioning
confidence: 99%